miRNA Regulation of Glutathione Homeostasis in Cancer Initiation, Progression and Therapy Resistance - Marengo, Barbara (Microrna, 2020)
Glutathione (GSH) is the most abundant antioxidant that contributes to regulating the cellular production of Reactive Oxygen Species (ROS) which, maintained at physiological levels, can exert a function of second messengers in living organisms. In fact, it has been demonstrated that moderate amounts of ROS can activate the signaling pathways involved in cell growth and proliferation, while high levels of ROS induce DNA damage leading to cancer development. Therefore, GSH is a crucial player in the maintenance of redox homeostasis and its metabolism has a role in tumor initiation, progression, and therapy resistance. Our recent studies demonstrated that neuroblastoma cells resistant to etoposide, a common chemotherapeutic drug, show a partial monoallelic deletion of the locus coding for miRNA 15a and 16-1 leading to a loss of these miRNAs and the activation of GSH-dependent responses. Therefore, the aim of this review is to highlight the role of specific miRNAs in the modulation of intracellular GSH levels in order to take into consideration the use of modulators of miRNA expression as a useful strategy to better sensitize tumors to current therapies.